Blue-phase liquid crystal display with insulating protrusion. Issue 11 (2nd September 2018) - Guo, Yuqiang; Wang, Yifei; Zhang, Chi; Mu, Qihui; Li, Xiaoshuai; Sun, Yubao; Dou, Hu; Wang, Qionghua
ABSTRACT: In order to lower the saturation voltage and enhance the transmittance of in-plane switching blue-phase liquid crystal display (IPS-BPLCD), IPS-BPLCD with insulating protrusion is proposed. The single-protrusion (only set on the top of pixel electrode) and double-protrusion (set on the top of pixel and common electrodes) structures are investigated in this work. The potential distribution changes when the protrusion is used. There is a thicker transverse electric field in BPLC range, because the stronger electric field at the edges of the electrodes is decentralised into BPLC range. As a result, the saturation voltage is reduced from 36.3 V to 28.9 V when the double-protrusion structure is used, and transmittance is increased by ~20%. The contrast ratio is larger than 1000:1 in 60° viewing cone using a half-wave biaxial film. Both single-protrusion and double-protrusion structures have the uniform gamma curves at large oblique viewing angles. Moreover, the off-axis image distortion index is 0.1590 at 60º polar angle when zigzag electrodes are used. Graphical Abstract: